The impact of household capital income on income inequality: A factor decomposition analysis for Great Britain, Germany and the USA - Anna Fräßdorf; Markus M. Grabka; Johannes Schwarze (Institute for the Study of Labor (IZA), 2008)
This paper analyses the contribution of capital income to income inequality in a cross-national comparison. Using micro-data from the Cross-National Equivalent File (CNEF) for three prominent panel studies, namely the BHPS for Great Britain, the SOEP for West Germany, and the PSID for the USA, a factor decomposition method described by Shorrocks (1982) is applied. The factor decomposition of disposable income into single income components shows that capital income is exceedingly volatile and its share in disposable income has risen in recent years. Moreover, capital income makes a disproportionately high contribution to overall inequality in relation to its share in disposable income. This applies to Germany and the USA in particular. Thus capital income accounts for a large part of disparity in all three countries.
urn:nbn:de:101:1-20080527129
Keywords: D33; 330; Inequality; capital income; factor decomposition; CNEF; Haushaltseinkommen; Kapitalertrag; Einkommensverteilung; Dekompositionsverfahren; Großbritannien; Deutschland; USA